Examining the impact of a restorative breath-based intervention “Sudarshan Kriya Yoga” at work: a field experiment - Chhajer, Raina; Dagar, Chirag (Frontiers in Psychology, 2024)
Background Human capital plays a crucial role in the success of an organization and further contributes to the broader goals of growth and development of society. In this regard, it is essential to ensure the well-being of employees at the workplace. Given the positive impact of yoga on psycho-physiological aspects of health, this study aims to examine the impact of a breath-based yogic intervention, Sudarshan Kriya Yoga (SKY), on stress, anxiety, thriving, general health, emotional well-being, social well-being, and psychological well-being among employees of a leading manufacturing firm in India. Methods Undertaking a randomized-control experiment design (n = 64), we examined the impact of SKY on stress, anxiety, thriving, general health, and emotional, social, and psychological well-being. Two certified instructors conducted the SKY intervention in a retreat format over 3 days. Results The analysis demonstrated positive outcomes across various aspects of participants’ well-being, i.e., it significantly reduced their stress and anxiety and increased the levels of thriving, general health, and emotional, social, and psychological well-being. These findings are valuable for understanding the potential benefits of the SKY intervention. Discussion The findings provide support for considering SKY as a potential well-being intervention for employers at the workplace and society at large. Further exploration, implementation, and research in diverse contexts will be crucial to fully understand the long-term impact and scalability of the SKY intervention in promoting holistic well-being.